Factors associated with all-cause mortality in tuberculosis patients in a Malaysian tertiary hospital - Wong, Chee Kuan; Ng, Kee Seong; Choo, Sarah Qian Rou; Lee, Choon Jiat; Teo, Yik Pheng; Liew, Su May; Chinna, Karuthan; Khoo, Ee Ming; Ng, Wei Leik; Tok, Peter Seah Keng; Kee, Yan Shen; Chiang, De Min (The Journal of Infection in Developing Countries, 2023)
Introduction: The all-cause mortality for tuberculosis is 1 in every 10 patients in Malaysia. The currently available national surveillance database does not record patients’ variables such as socio-economic factors, existing co-morbidities, and risk behavior for investigation. An electronic medical record system can capture this missing information and use it to determine all-cause mortality factors more accurately. Our study aims to determine the factors associated with all-cause mortality in a cohort of tuberculosis patients in a Malaysian tertiary hospital which is equipped with an electronic medical record system. Methodology: Records of patients diagnosed with tuberculosis from 1st January 2018 to 30th September 2019 were retrieved. Sociodemographic and clinical data were extracted. Treatment outcomes and all-cause mortality were recorded at 1 year after diagnosis. Univariate, multivariate, and stepwise regression were used to determine the factors associated with all-cause mortality. Results: Four-hundred and seventy-one patients were reviewed. The mean age was 46.6 ± 19.7 years. The all-cause mortality rate at one year of diagnosis was 15.3%. Factors identified were age [aOR 1.026 (95% CI: 1.004-1.049)], chronic kidney disease [aOR 3.269 (1.508-7.088)], HIV positive status [aOR 4.743 (1.505-14.953)], active cancer [aOR 5.758 (1.605-20.652)], liver disease [aOR 6.220 (1.028-37.621)], and moderate to advanced chest X-ray findings [aOR 3.851 (1.033-14.354)]. Conclusions: On average, one in seven patients diagnosed with TB died within a year in a Malaysian tertiary hospital. Identification of this vulnerable group using the associated factors found in this study may help to reduce the risk of mortality through early intervention strategies.